2015
DOI: 10.1039/c4cp03631j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced visible light photocatalytic activity of Cu2O via cationic–anionic passivated codoping

Abstract: To improve the photocatalytic activity of Cu2O for hydrogen production through water splitting, the band edges of Cu2O should be modified to meet the electronic transition of angular momentum selection rules (Δl = ±1) and match with the hydrogen or oxygen production levels. Upon analyzing the band structure of Cu2O and the chemical potentials of the dopants, we show that passivated codopants such as (Sn + B) can induce superior modification in the band edges of Cu2O: the conduction band edge is changed from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…The stability of co‐ and ternary‐doped systems is investigated by calculating their defect binding energies according to Equations : Enormalb = E|normalC + normalS + E|normalpnormalunormalrnormale E|normalC Etrue(normalStrue) Enormalb = E|normalFnormale + normalCtrue(normalonormalrnormalStrue) + E|normalpnormalunormalrnormale E|normalFnormale Etrue(normalCtrue(normalonormalrtrue(normalStrue)true) Enormalb = E|normalFnormale + normalC + normalS + E|normalpnormalunormalrnormale E|normalFnormale E|normalC Etrue(normalStrue) where E|normalFnormale + normalC+normalS, E|normalC + normalS, E|normalpnormalunormalrnormale, E|normalC, Etrue(normalStrue), and Etrue(normalFnormaletrue) represent the total energy of Fe/C/S ternary‐doped TiO 2 , C/S co‐doped TiO 2 , un‐doped TiO 2 , C, S, and Fe mono‐doped TiO 2 , respectively. Positive defect binding energy signifies strong tendency for the impure atoms to bind to each other …”
Section: Resultsmentioning
confidence: 99%
“…The stability of co‐ and ternary‐doped systems is investigated by calculating their defect binding energies according to Equations : Enormalb = E|normalC + normalS + E|normalpnormalunormalrnormale E|normalC Etrue(normalStrue) Enormalb = E|normalFnormale + normalCtrue(normalonormalrnormalStrue) + E|normalpnormalunormalrnormale E|normalFnormale Etrue(normalCtrue(normalonormalrtrue(normalStrue)true) Enormalb = E|normalFnormale + normalC + normalS + E|normalpnormalunormalrnormale E|normalFnormale E|normalC Etrue(normalStrue) where E|normalFnormale + normalC+normalS, E|normalC + normalS, E|normalpnormalunormalrnormale, E|normalC, Etrue(normalStrue), and Etrue(normalFnormaletrue) represent the total energy of Fe/C/S ternary‐doped TiO 2 , C/S co‐doped TiO 2 , un‐doped TiO 2 , C, S, and Fe mono‐doped TiO 2 , respectively. Positive defect binding energy signifies strong tendency for the impure atoms to bind to each other …”
Section: Resultsmentioning
confidence: 99%
“…[49][50][51][52][53][54][55] Such ac odopinga pproachi sa lso effective to enhance the visible-light photocatalytic activity of Cu 2 Ob y changing the even-parity symmetry of the CBM to odd-parity symmetry to meet the angular selection rule of electronic transitions. [56] Erünale tal. investigated the interplay between aliovalent CuO doping and nonstoichiometry on the development of defect structuresa nd the formation of secondary phases of antiferroelectric NaNbO 3 ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…We first built 2 × 1 × 2 supercells ( a = 9.188 Å, b = 4.594 Å, c = 5.918 Å) as an initial structure model of a defect‐free TiO 2 layer through a primitive cell of rutile TiO 2 ( a = b = 4.594 Å, c = 2.959 Å), as Fig. a shows . Then, other 2 × 1 × 2 supercells of defect‐free Cu 2 O layer ( a = 8.5392 Å, b = 4.2696 Å, c = 8.5392 Å) were built on a primitive cell of Cu 2 O ( a = b = c = 4.2696 Å), as Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Robert and coworkers investigated the impact of different amounts of Cu 2 O on the photocatalytic activity of Cu x O/TiO 2 heterojunctions and found the high efficiency for photodecomposition of Orange II . About the visible‐light photocatalytic activity of Cu 2 O, Jiang et al concluded that it could be enhanced by changing the odd–even property of the conduction‐band edge of Cu 2 O via Sn + B passivated codoping. Following these studies, we here carry out first‐principles calculations to investigate the impact of dopants at the interface of Cu x O/TiO 2 heterojunctions on the visible‐light absorption.…”
Section: Introductionmentioning
confidence: 99%